2012
DOI: 10.3171/2012.2.focus1218
|View full text |Cite
|
Sign up to set email alerts
|

Spinal dural arteriovenous fistulas: outcome and prognostic factors

Abstract: The aim of this study is to review the clinical outcome of patients treated for spinal dural arteriovenous malformations and investigate the presence of pretreatment indicators of outcome after short- and midterm follow-up. The authors retrospectively reviewed the records of 65 consecutive patients treated either surgically or endovascularly in 3 neurosurgery departments between 1989 and 2009. After treatment, 80% of patients reported improvement of at least 1 symptom. Motor symptoms improved more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 26 publications
0
40
1
3
Order By: Relevance
“…While delayed diagnosis was not an independent predictor of poor postoperative outcome in the Cenzato series, it was associated with a higher degree of disability at the time of treatment and thus a poorer clinical outcome following treatment. 17 A previous analysis of 153 patients with SDAVF treated surgically at our institution did not find an independent association between the time from symptom onset to fistula treatment and postoperative prognosis; however, preoperative disability was the strongest determinant of postoperative outcome. 18 In the current study focused on patients with delayed diagnosis, treatment very often took place only once substantial disability had already developed, and all too frequently this disability proved irreversible despite successful obliteration of the fistula.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While delayed diagnosis was not an independent predictor of poor postoperative outcome in the Cenzato series, it was associated with a higher degree of disability at the time of treatment and thus a poorer clinical outcome following treatment. 17 A previous analysis of 153 patients with SDAVF treated surgically at our institution did not find an independent association between the time from symptom onset to fistula treatment and postoperative prognosis; however, preoperative disability was the strongest determinant of postoperative outcome. 18 In the current study focused on patients with delayed diagnosis, treatment very often took place only once substantial disability had already developed, and all too frequently this disability proved irreversible despite successful obliteration of the fistula.…”
Section: Discussionmentioning
confidence: 98%
“…All 7 patients had become wheelchair-bound by the time of treatment, and 4 remained nonambulatory after treatment of the fistula and rehabilitation. Cenzato et al 17 reviewed 65 patients with SDAVFs undergoing surgical and endovascular treatment and found that patients with the best clinical outcomes were those who had been diagnosed early and had an Aminoff scale score of Ͻ3 before the intervention. While delayed diagnosis was not an independent predictor of poor postoperative outcome in the Cenzato series, it was associated with a higher degree of disability at the time of treatment and thus a poorer clinical outcome following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is suitable for almost every kind of vascular lesion. It is thought to be the "first-line" therapy for dural AVF, with low to no complications [40,41]. Despite the fact that many report excellent results after endovascular therapy, a higher rate of recurrence and partial improvement is observed [5,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that many report excellent results after endovascular therapy, a higher rate of recurrence and partial improvement is observed [5,7,10]. The localization of the dural AVF is believed to be a predictive factor for the outcome [40]. A better improvement, however, is observed in patients with better preoperative neurological function, which also presents a significant predictive factor for the surgery and generally for the outcome [4,42].…”
Section: Discussionmentioning
confidence: 99%
“…Typically these patients present with back pain and sensory or motor changes over months to years. 5,16 In rare cases, patients younger than 30 years of age can present with sudden myelopathy secondary to hemorrhage. 6,11 Coup de poignard of Michon refers to sudden back pain due to rupture of an SVM, akin to the thunderclap headache of aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%